Sleep-Disordered Breathing Is Associated With Impaired Odor Identification in Older U.S. Adults - Siegel, Jesse K (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Sleep-disordered breathing (SDB) is a common, underdiagnosed condition in older adults with major health consequences, including disrupted central nervous system functioning. Whether SDB may affect sensory function is unclear. We sought to address this question by comparing 2 forms of olfactory testing which measure peripheral and central olfactory processing. METHODS: We assessed SDB (survey-reported snoring frequency, nighttime apneic events, or diagnosis of sleep apnea) in the National Social Life, Health, and Aging Project, a nationally representative sample of older U.S. adults. Odor sensitivity (peripheral) and odor identification (central) were assessed with validated instruments. Logistic regression was used to test the relationship between SDB and olfaction, accounting for relevant covariates, including demographics, cognition, and comorbidity. RESULTS: Twenty-nine percent of older U.S. adults reported symptoms of SDB (apneic events or nightly snoring). Of these, only 32% had been diagnosed with sleep apnea. Older adults with SDB (those who reported symptoms or have been diagnosed with sleep apnea) were significantly more likely to have impaired odor identification (odds ratio 2.13, 95% confidence interval 1.19–3.83, p = .012) in analyses that accounted for age, gender, race/ethnicity, education, cognition, comorbidities (including depression), and body mass index. Presence of SDB was not associated with impaired odor sensitivity (odds ratio 1.03, 95% confidence interval 0.75–1.43, p = .84). CONCLUSION: SDB is highly prevalent but underdiagnosed in older U.S. adults and is associated with impaired odor identification but not odor sensitivity. These data support the concept that SDB affects pathways in the central nervous system which involve chemosensory processing.